Euphemism In Indonesian Movie Reviews: A Sociolinguistics Study - Haryani, Heni; Fikri F, Deri (CV RIFAINSTITUT, 2025)
This research investigates the euphemism strategies employed by content creators in their movie reviews. Given the growing influence of online content creators on consumer behavior, it is crucial to examine how they utilize language techniques to shape their reviews. Using a descriptive qualitative approach, this study aims to identify the specific types and purposes of euphemisms used by content creators when evaluating films. The findings reveal that content creators primarily rely on the substitution and periphrasis types of euphemisms, where substitution involves replacing potentially offensive or sensitive terms with more palatable alternatives, and periphrasis uses roundabout expressions to convey meaning. Notably, the research also indicates that the primary purpose behind the use of these euphemistic techniques is to captivate the audience's attention. By mapping the euphemism strategies of content creators in the context of movie reviews, this study contributes to the broader understanding of euphemism usage across different domains, informing discussions on the ethical considerations and impact of language choices in influential digital content, and laying the groundwork for further exploration of euphemism practices in various content creation and communication settings